Peranan Generasi Z dalam Event Jimbafest 2023 di Jimbaran Hijau - Prianta, Putu Agung; Sulistyawati, Anastasia (Journal of Tourism and Creativity, 2024)
One strategy to optimize Gen Z employees as organizational assets is to utilize them by placing Gen Z according to their roles. HRD must be able to assess employee competencies and capabilities so that they can assign them the right position, because balancing roles in teamwork is important to create a conducive work environment and productive collaboration. This research aims to determine the role of Generation Z teamwork at the Jimbafest event and identify the role of Gen Z that needs to be improved so that the event can run more optimally. This research uses a mix of methods, including JMP software and data collection via questionnaires. The research results show that the roles of Plant, Specialist, and Resource Investigator are very lacking and must be improved to be able to create more productive work teams and complete work more effectively. Generation Z who contribute to a performance or activity must be more creative and imaginative in coming up with brilliant ideas, have experience and in-depth understanding in their field, and must be able to be good networkers or facilitators.